OSTEOARTHRITIS IN PATIENTS WITH METABOLIC SYNDROME IN THE PRACTICE OF A FAMILY DOCTOR - Zhdan, V.M.; Lebid, V.G.; Babanina, M.Yu; Kyrian, O.A.; Volchenko, G.V.; Ivanytsky, I.V.; Tkachenko, M.V. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Introduction. The problem of osteoarthritis is of considerable clinical significance, as it, along with ischemic heart disease and arterial hypertension, forms a triad of the most prevalent chronic conditions among middle-aged and elderly populations. Osteoarthritis is one of the most widespread joint disorders globally. Therefore, it is essential to develop effective algorithms for family physicians to diagnose, manage, and prevent osteoarthritis, particularly when it is associated with metabolic syndrome. Such approaches can help reduce symptoms, improve joint function, prolong periods of remission, and ultimately enhance patients’ quality of life. Purpose: to conduct a literature review and highlight modern aspects of treatment and monitoring of osteoarthritis combined with metabolic syndrome in the practice of family doctors. Materials and methods: A literature search was conducted using both printed and electronic sources, including the scientific databases Medline and PubMed. The methods of analysis, comparison, and generalization were applied to identify relevant publications. The review focused on articles related to the monitoring and treatment of osteoarthritis in combination with metabolic syndrome, specifically within the context of family medicine practice. Results. This review highlights the clinical relevance of osteoarthritis, along with current data on the prevalence of both osteoarthritis and metabolic syndrome. Classification criteria and functional assessment scales for joint evaluation are presented. The authors examine the latest recommendations from the American College of Rheumatology and the European League Against Rheumatism regarding the diagnosis and management of osteoarthritis. An evidence-based algorithm is proposed for family physicians, detailing modern approaches to diagnosis, the prescription of combination pharmacotherapy, and preventive strategies for osteoarthritis associated with metabolic syndrome. Additionally, recent scientific studies exploring the relationship between osteoarthritis and metabolic syndrome are analyzed, offering prospects for the development of new diagnostic, therapeutic, and preventive approaches. Conclusions. The comorbidity of osteoarthritis and metabolic syndrome remains a significant concern in modern rheumatology, presenting numerous unresolved questions and research directions. The implementation of a clear, evidence-based algorithm for family physicians encompassing modern diagnostic methods, combined pharmacological treatment, and preventive strategies must be grounded in a thorough understanding of the shared pathogenesis of these conditions. Such an approach holds the potential to improve disease outcomes and extend periods of remission in affected patients. Continued efforts are essential to support the integration of up-to-date diagnostic and therapeutic techniques into routine family medicine practice for the effective management of osteoarthritis and metabolic syndrome.